A Scoping Review of Perinatal Recreational Drug Use: Methods, Socio-Demographic Characteristics and Commonly Used Drugs - Ndegwa, Marcellina; Baya Msanzu, Joseph; Budambula, Valentine (Multidisciplinary Journal of Technical University of Mombasa, 2023)
Perinatal recreational drug use is a leading cause to poor pregnancy out comes, increased maternal, foetal or neonatal morbidity and mortality. This review paper sought to identify socio-demographic determinants of perinatal drug use, commonly used drugs by perinatal mothers and methods used to assess drug use. We retrieved information from ten data bases namely: PubMed, Google Scholar, Scopus, Web of Science, CDC library, WHO library, Wiley Online library, Springer Link Scientific Reports, Bio Med Central and National Library of Medicine. Inclusion criterion was studies that were designed to document perinatal drug use and studies published in English between January 2012 and February 2023. A total of 27 studies were reviewed distributed as follows: America (6), Europe (4), Australia (1), New Zealand (1), Asia (1), South Africa (3), West Africa (2) and East Africa (10). Out of all the 28 studies, 24 were based on self-reported history, 4 were anchored on blood, hair, urine and meconium toxicology while 3 used both self-reported history plus confirmed drug use approach. Key socio-demographic characteristics that predicted perinatal drug use were low income, unemployment, low level of education, single parenthood, multiple sexual partnerships, having a partner or friend who uses drugs, having experienced intimate partner violence and pre-pregnancy drug use. On the other hand, maternal stress, depression, anxiety, loneliness and history of mental illness influenced drug use in this sub-population. Alcohol was the most commonly used drug globally. Others were Cannabis, tobacco products, methamphetamine, cocaine, amphetamine/khat and heroin. We recommend screening of drug use during the perinatal period using more than one method, routine assessment of mental distress and provision of targeted counseling to perinatal mothers in distress. Further, we recommend enhanced targeted health education on risks associated with drug use during perinatal period and more research on perinatal recreational drug use.